Negating negation against the apophatic abandonment of the Dionysian Corpus - Knepper, Timothy D. (Cambridge : James Clarke, 2014)
Negating Negation'' critically examines key concepts in the corpus of Pseudo-Dionysius the Areopagite: divine names and perceptible symbols; removal and negation; hierarchy and hierurgy; ineffability and incomprehensibility. In each case it argues that the Dionysian corpus does not negate all things of an absolutely ineffable God; rather, it negates few things of a God that is effable in important ways. Dionysian divine names are not inadequate metaphors or impotent attributes but transcendent divine causes. Divine names are not therefore flatly negated of God but removed as ordinary propertie.
Front Cover; Title Page; Copyright Information; Contents; Tables; Preface; Introduction; Chapter 1. The Divine Names Are Not Names; Chapter 2. Negation Does Not Negate; Chapter 3. Ranks Are Not Bypassed; Rites Are Not Negated; Chapter 4. The Ineffable God Is Not Ineffable; Conclusion; Bibliography; Back Cover.
Includes bibliographical references and index.
Description based on CIP data; item not viewed.
Master record variable field(s) change: 072
Keywords: Pseudo-Dionysius, -- the Areopagite; Negative theology -- Christianity -- History of doctrines; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Mysticism; Negative theology; Neoplatonism; Pseudo-Dionysius, the Areopagite -- Criticism, interpretation, etc; PHILOSOPHY / Religious; Electronic books